CAUSES OF COMPLEMENTARY FOODS GIVEN TO BABIES AGED 0-6 MONTHS IN PAYA PASIR, MEDAN MARELAN DISTRICT - Debora Lestari Simamora; Ida Yustina; R. Kintoko Rochadi; Nurmaini Nurmaini; Fikarwin Zuska (International Journal of Midwifery Research, 2023)
The majority of experts accept that complementary foods shouldn't be introduced before 4 months of age, despite inconsistent advice regarding the best time to do so. Regardless of recommendations, studies show that 20% to 40% of infants in the US start eating before they are 4 months old. Previous research was non-representative of the country and concentrated on the introduction of solid foods. While baby-led weaning (BLW) is a popular complementary feeding practice, evidence supporting the potential benefits and/or risks for infant growth, development, and health could be considered. The research method is qualitative with a phenomenological approach. Thematic analysis was used with the help of the Nvivo 12 Plus software. The findings of this study indicated three major themes regarding the causes of complementary feeding: inadequate knowledge, working mothers, and slow baby growth. The purpose of this study is to provide evidence-based guidelines and increase mothers' knowledge about the benefits of complementary foods in infants aged 0–6 months